Antibacterial activity of probiotic bacteria against pathogenic bacteria isolated from different chicken organs - Soliman, Aya M.; Ghaly, Mohamed F.; Elariny, Eman Y. (Journal of Advanced Veterinary Research, 2024)
Even though a wide variety of antimicrobial medications have been discovered and developed, multidrug resistance still poses a severe threat to public health and is continuously increasing mortality. Recently, a lot of research has focused on developing solutions to these problems. In this paper, we demonstrated how various antibiotics can be combined with antimicrobial substances like LAB and plant extracts to provide synergistic effects if each therapy concentrates on a different target or signalling pathway and acts via a different mechanism. MDR bacteria were isolated from chicken organs using standard methods, and they were confirmed using 16S RNA. In Al-Sharkia Governorate, Egypt, 100 different samples of chicken organs (including the breast, drumstick, liver, wings, skin, intestine, pins, giblets, heart, and legs) were taken at random from six different sites. Bacillus was the associated pathogenic bacteria obtained from the isolated chicken organs and was confirmed using molecular, biochemical, and microbiological techniques. The most efficient extracts that proved to have bacteriostatic and bactericidal properties against the highly resistant strains of pathogenic bacteria were found to be the Lactobacillus plantarum EMCC1027. The LAB applied in the study has excellent antibacterial properties and can be used as a safe substitute for antibiotics to inhibit the growth of the food-borne pathogens.